Beginner's Luck : Dispatches from the Klamath Mountains - Terence, Malcolm (Book collections on Project MUSE., 2018)
"Explores the author's life in a commune at Black Bear Ranch, established in a remote area of the Klamath Mountains near the California-Oregon border in the 1960s, and his subsequent move to a nearby rural town, where he worked variously logging, gold mining, and growing marijuana, all the while negotiating complex relationships with the local residents, including Native American population."--Provided by publisher.